2020
DOI: 10.12659/msm.923934
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Hub Genes and Pathways In Esophageal Carcinoma Based on NCBI’s Gene Expression Omnibus (GEO) Database: A Bioinformatics Analysis

Abstract: Background Esophageal carcinoma (ESCA) is a health challenge with poor prognosis and limited treatment options. Our aim is to screen for hub genes and pathways associated with ESCA pathology as diagnostic or therapeutic targets. Material/Methods We downloaded 2 ESCA-related datasets from the Gene Expression Omnibus (GEO) database. Subsequently, differentially expressed genes (DEGs) of ESCA were determined by statistical analysis. Both Gene Ontology (GO) and Kyoto Encycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…Key miRNAs and target genes have been reported to be mainly related to the PI3K–Akt signaling pathway in GI cancers ( Lai et al, 2019 ). A bioinformatics analysis showed that the DEGs of EC compared with normal tissues are mainly enriched in the PI3K–Akt signaling pathway ( Li M. et al, 2020 ; Yu-Jing et al, 2020 ). Moreover, GLI1 co-expressed and DEGs between tumor samples and normal tissues were both largely enriched in the PI3K–Akt pathway in STAD ( Yu et al, 2018 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Key miRNAs and target genes have been reported to be mainly related to the PI3K–Akt signaling pathway in GI cancers ( Lai et al, 2019 ). A bioinformatics analysis showed that the DEGs of EC compared with normal tissues are mainly enriched in the PI3K–Akt signaling pathway ( Li M. et al, 2020 ; Yu-Jing et al, 2020 ). Moreover, GLI1 co-expressed and DEGs between tumor samples and normal tissues were both largely enriched in the PI3K–Akt pathway in STAD ( Yu et al, 2018 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GEO database (https://www.ncbi.nlm.nih.gov/geo/) is a publicly available database of gene expression data that stores a large amount of microarray data [12]. Six datasets from the GEO database (GSE23400, GSE20347, GSE29001, GSE53625, GSE45670 and GSE26886) were used to determine PPFIA1 mRNA expression in ESCC and normal tissues.…”
Section: The Geo Databasementioning
confidence: 99%
“…The GEO database is a publicly available database of gene expression data that stores a large amount of microarray data (https://www.ncbi.nlm.nih.gov/geo/) [11]. Six datasets from the GEO database (GSE23400, GSE20347, GSE29001, GSE53625, GSE45670 and GSE26886) were used to determine PPFIA1 mRNA expression in ESCC and normal tissues.…”
Section: The Geo Databasementioning
confidence: 99%